A solvent-resistant azide-based hole injection/transporting conjugated polymer for fluorescent and phosphorescent light-emitting diodes1. Issue 31 (21st August 2015) - Huang, Cheng-Wei; Chang, Feng-Chih; Chu, Yu-Lin; Lai, Cheng-Chang; Lin, Tzu-En; Zhu, Chao-Yuan; Kuo, Shiao-Wei
<x xml:space="preserve">Abstract</x> A simple methodology for overcoming interfacial mixing, based on the use of a photo-crosslinkable conjugated polymer as HITM for fluorescent and solution-processed phosphorescent OLEDs.